In search of phonotactic preferences - Orzechowska, Paula (Yearbook of the Poznan Linguistic Meeting, 2016)
The objective of this contribution is to provide an analysis of consonant clusters based on the assumption that phonotactic preferences are encoded in phonological features of individual segments forming a cluster. This encoding is expressed by a set of parameters established for the following features: complexity, place of articulation, manner of articulation and voicing. On the basis of empirically observed tendencies of feature distribution and co-occurrence, novel phonotactic preferences for English word-initial consonant clusters are proposed. Statistical methods allow us to weigh the preferences and determine a ranking of phonological features in cluster formation.